Indonesia‘s Refining Developments: Future Prospects and Challenges - Maizar Rahman (Scientific Contributions Oil and Gas, 2010)
Since 1994 Indonesia has not built any new refineries due to the economic crisis in1998, which was followed by political reform. Last year Indonesia had imported more than400 thousand bpd (barrel per day) of petroleum products. On the supply side, Pertamina’srefinery capacity of 1,050 thousand bpd produces only up to 750 thousand bpd of petroleumfuels or 68 % of domestic consumption.A study has been conducted on the refining development in Indonesia up to year 2030.According to a projection based on reference scenario, in year 2030 Indonesia will consume2.60 million bpd of petroleum fuels. If security of supply approach is taken intoconsideration, Indonesia will require 3 million bpd of total refinery capacity. New refineriesproducing additional 2 million bpd have to be constructed in order to fulfill domesticdemand for petroleum fuels. The additional new refineries would then be on-stream one byone with 300 thousand bpd of capacity starting from year 2015, and would be built nearconsumers’ area or close to the existing refineries.As the margin of new refinery is not high enough, appropriate strategies such as optimumconfiguration, synergy to utilize possible supporting resources should be taken intoconsideration, while Indonesian government should also offers better incentives in orderto make the project economically feasible.